Epidemiological aspects in trophic ulcers with methicillin-resistant Staphylococcus - PRISACARI, Viorel; BUGA, Diana; BERDEU, Ion (One Health & Risk Management, 2021)
Introduction. Trophic ulcer continues to be a major clinical problem, currently having a significant socio-economic impact. The association of microbial infections, especially with antibiotic-resistant bacteria, is one of the most common complications of trophic ulcers. In this context, trophic ulcers associated with methicillin-resistant Staphylococcus (MRS) have a high epidemiological and clinical significance. Material and methods. The determination of risk factors, antimicrobial resistance, as well as the clinical and socio-economic impact of trophic ulcers caused by MRS strains was performed based on a retrospective case-control study. The research group included 52 observation sheets of patients with trophic ulcers caused by methicillin-resistant Staphylococcus (MRS), the control group - 39 sheets of patients with trophic ulcers caused by methicillin-sensitive Staphylococcus (MSS). Results. MRS strains isolated from trophic ulcers had high rates of antibiotic resistance compared to MSS strains. As a risk factors of trophic ulcer from which MRS strains have been isolated, people over the age of 50, repeated hospitalizations, microbial associations and exposure to intensive care are highlighted.Conclusions. Risk factors and local epidemiology knowledge in trophic ulcers with MRS is the key factor in implementing and complying with surveillance and control measures.